O amor no sertão rosiano: uma leitura de Desenredo e Dão-Lalalão - Rissi, Natália Calderan (2020)
This work proposes to analyze the novella Dão-Lalalão, present in the book Noites do Sertão, which is part of the work Corpo de Baile, and the short story Desenredo, present in the book Tutameia, by João Guimarães Rosa. Our proposal is to understand how love is presented in these narratives, taking into account the historical and social context of the backlands. Starting from these two elements, love and the backlands, which we consider fundamental to understand the writer, this study proposes a new reading of these narratives, which discusses the love inserted in the social and political environment of the backlands, in which both concepts can’t be understood separately. Thus, the questions that motivate this research are: how is love shown in these narratives, where, less or more explicitly, there is the determination of social order, predominated by the jagunço system? Why do the protagonists, Jó Joaquim and Soropita, find different solutions to deal with their love relationships, taking into account that both of them love women who do not correspond - or did not correspond - the model of women expected in the backlands?In other words, we seek to understand how love occurs in this particular historical environment and what are the implications for Soropita, the protagonist of Dão-Lalalão, who succumbs to the discontentment, and for Jó Joaquim, the protagonist of Desenredo, who can forgive the woman he loves and find happiness through love.